Allogeneic hematopoietic stem cell transplantation allows long-term complete remission and curability in high-risk Waldenström’s macroglobulinemia: results of a retrospective analysis of the Société Française de Greffe de Moelle et de Thérapie Cellulaire - Garnier, Alice; Robin, Marie; Larosa, Fabrice; Golmard, Jean-Louis; Gouill, Steven Le; Coiteux, Valérie; Tabrizi, Reza; Bulabois, Claude-Eric; Cacheux, Victoria; Kuentz, Mathieu; Dreyfus, Brigitte; Dreger, Peter; et al. (Haematologica, the hematology journal, 2010)
Background Patients with poor-risk Waldenström’s macroglobulinemia have suboptimal response and early post-treatment relapse with conventional therapies. Hence, new therapeutic approaches such as allogeneic stem cell transplantation should be evaluated in these patients.Design and Methods We examined the long-term outcome of allogeneic stem cell transplantation in Waldenström’s macroglobulinemia by studying the records of 24 patients reported in the SFGM-TC database and one transplanted in the bone marrow unit in Hamburg.Results Median age at the time of transplant was 48 years (range, 24-64). The patients had previously received a median of 3 lines of therapy (range, 1-6) and 44% of them had refractory disease at time of transplant. Allogeneic stem cell transplantation after myeloablative (n=12) or reduced-intensity (n=13) conditioning yielded an overall response rate of 92% and immunofixation-negative complete remission in 50% of evaluable patients. With a median follow-up of 64 months among survivors (range, 11-149 months), 5-year overall survival and progression-free survival rates were respectively, 67% (95% CI: 46-81) and 58% (95% CI: 38-75). The 5-year estimated risk of progression was 25% (95% CI: 10-36%), with only one relapse among the 12 patients who entered complete remission, versus 5 in the 12 patients who did not. Only one of the 6 relapses occurred more than three years post-transplant.Conclusions Allogeneic stem cell transplantation yields a high rate of complete remissions and is potentially curative in poor-risk Waldenström’s macroglobulinemia.
Gesehen am 10.10.2023